Preoperative rectal cancer staging with phased-array MR - Giusti Sabina; Buccianti Piero; Castagna Maura; Fruzzetti Elena; Fattori Silvia; Castelluccio Elisa; Caramella Davide; Bartolozzi Carlo (Radiation Oncology, 2012)
Abstract Background We retrospectively reviewed magnetic resonance (MR) images of 96 patients with diagnosis of rectal cancer to evaluate tumour stage (T stage), involvement of mesorectal fascia (MRF), and nodal metastasis (N stage). Our gold standard was histopathology. Methods All studies were performed with 1.5-T MR system (Symphony; Siemens Medical System, Erlangen, Germany) by using a phased-array coil. Our population was subdivided into two groups: the first one, formed by patients at T1-T2-T3, N0, M0 stage, whose underwent MR before surgery; the second group included patients at Tx N1 M0 and T3-T4 Nx M0 stage, whose underwent preoperative MR before neoadjuvant chemoradiation therapy and again 4-6 wks after the end of the treatment for the re-staging of disease. Our gold standard was histopathology. Results MR showed 81% overall agreement with histological findings for T and N stage prediction; for T stage, this rate increased up to 95% for pts of group I (48/96), while for group II (48/96) it decreased to 75%. Preoperative MR prediction of histologically involved MRF resulted very accurate (sensitivity 100%; specificity 100%) also after chemoradiation (sensitivity 100%; specificity 67%). Conclusions Phased-array MRI was able to clearly estimate the entire mesorectal fat and surrounding pelvic structures resulting the ideal technique for local preoperative rectal cancer staging.